2016
DOI: 10.1159/000447902
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Attenuates Foam Cell Formation and Apoptosis in Ox-LDL-Stimulated Macrophages by Enhancing Autophagy

Abstract: Background: Our previous studies demonstrated that luteolin, which is rich in flavones, has various biological properties and can exert anti-oxidant, anti-inflammatory and anti-apoptotic activities. However, its effect on ox-LDL-induced macrophage lipid accumulation and apoptosis has not been revealed. Aims: This study aimed to explore the role of luteolin in ox-LDL-induced macrophage-derived foam cell formation and apoptosis and to delineate the underlying mechanism. Methods: Murine RAW264.7 cells were stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 40 publications
(56 reference statements)
2
41
0
Order By: Relevance
“…The abnormal high cytoplasmic calcium level could result in mitochondrial permeability transition pore opening, ΔΨm decrease, and finally cause apoptosis of cardiomyocytes [32]. In addition, Lut can regulate cell apoptosis by enhancing autophagy [33, 34]. These may be the mechanism involved in the protective effect of Lut on I/R cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal high cytoplasmic calcium level could result in mitochondrial permeability transition pore opening, ΔΨm decrease, and finally cause apoptosis of cardiomyocytes [32]. In addition, Lut can regulate cell apoptosis by enhancing autophagy [33, 34]. These may be the mechanism involved in the protective effect of Lut on I/R cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In human osteosarcoma U2OS cells, luteolin enhanced doxorubicin-induced autophagy [30]. In addition, luteolin treatment could stimulate autophagy in a Parkinson’s disease model, in post-infarction cardiac dysfunction, and in foam cell formation [31-33]. …”
Section: Discussionmentioning
confidence: 99%
“…Luteolin (3’,4,’5,’7’-tetrahydroxyflavone, Lut) is a natural, soluble flavone that is found in high levels in many plants, such as vegetables, fruits and herbs, and it exerts anti-tumor, anti-inflammatory and anti-apoptotic activities [19-21]. Our preliminary experiments found that luteolin suppressed p38 MAPK activation when a pretreatment was administered before I/R.…”
Section: Introductionmentioning
confidence: 99%